The Application Of Maslahah In Islamic Finance And Banking Products & Fatwa Resolutions In Malaysia - Bakar, Marina Abu; Rahim, Ahmad Khilmy Abdul; Ismail, Che Zuina (The journal of contemporary issues in business and government, 2021)
From time to time, maslahah is one of the sources of Islamic law that is often used after the death of Prophet Muhammad PBUH to develop Shariah principles in line with the needs and wants of human beings. In fact, this concept of maslahah is not something new as it was discussed previously by the classical and contemporary Muslim scholars. In addition, it becomes a key part that has been used in the determination of Shariah rules by Shariah advisors and experts in the matters that related to the benefits and needs of the people. The debate in general and the theory on this concept has laid a general basis and guide in applying it to current Islamic finance and banking issues. However, some scholars are on the opinion that the use of maslahahas a source of law today is found not to be fully comply with Shariah principles as outlined by the scholars of Islamic jurisprudence. Therefore, to maintain the resilience of Islamic financial and banking products, the standard criteria of maslahah must be determined and outlined wisely to avoid any future misuse of this concept pertaining to the Islamic law. Continuing from this issue, this study was conducted to analyze the application of maslahah in Islamic finance and banking and fatwa resolutions nowadays. Qualitative methods were used in this study with a library research approach. The collection of data includes sources of Islamic tradition such as classical and contemporary Islamic jurisprudence books. The process of analyzing the data is done using the content analysis method. The results of the study found that the concept of maslahah is primarily implemented in the context of Islamic finance and banking products and fatwa resolutions in Malaysia. Thus, it is also discovered that certain Islamic finance and banking products developed based on maslahah have fulfilled the maslahahstandard criteria stipulated by the Islamic law. This study is important in assisting the Shariah advisors and experts to determine the benchmark of maslahah concept that can be applied in Islamic finance and banking products and fatwa resolutions.